The Impact of Green Finance Initiatives on SME: A Systematic Literature Review - Andriyani, Kanya Azalia; Iwanda, M. Prayoga; Muharam, Harjum (LifeSciFi, 2025)
Amidst the growing global environmental concerns such as climate change, resource depletion, and pollution—sustainable business practices have become increasingly crucial. One strategic approach to gain traction in the financial sector for supporting sustainability goals is green finance. This financial instrument not only aims to channel capital towards environmentally friendly projects but also holds significant potential to support the development of SMEs. SMEs plays a vital role in the economic structure, particularly in developing countries, due to their contributions to economic growth, job creation, innovation, and market expansion. This study aims to review academic publications that examine the implementation of green finance within the SME sector and to systematically summarize existing findings to answer two key questions: the importance of implementing green finance in SMEs, and their impacts on SME development. Using the systematic literature review method, this study analyzes findings from various relevant articles to provide a comprehensive and structured understanding of the relationship between green finance, SME development, and sustainability. The findings in this study indicates that green finance implementation on SME yields positive effects on sustainability and SMEs development. This paper also uncover some factors that encourage green finance implementation and constraints that SMEs face when implementing them.